A disease-causing intronic point mutation C19G alters tau exon 10 splicing via RNA secondary structure rearrangement - Tan, Jiazi (2021)
Alternative splicing of MAPT cassette exon 10 produces tau isoforms with four microtubule-binding repeat domains (4R) upon exon inclusion or three repeats (3R) upon exon skipping. In human neurons, deviations from the ∼1:1 physiological 4R:3R ratio lead to frontotemporal dementia with Parkinsonism linked to chromosome 17 (FTDP-17). Certain FTDP-17-associated mutations affect a regulatory hairpin that sequesters the exon 10 5′ splice site (5′ss, located at the exon 10–intron 10 junction). These mutations tend to increase the 4R:3R ratio by destabilizing the hairpin, thereby improving 5′ss recognition by U1 snRNP. Interestingly, a single C-to-G mutation at the 19th nucleotide in intron 10 (C19G or +19G) decreases the level of exon 10 inclusion significantly from 56% to 1%, despite the disruption of a G-C base pair in the bottom stem of the hairpin. Here, we show by biophysical characterization, including thermal melting, fluorescence, and single-molecule mechanical unfolding using optical tweezers, that the +19G mutation alters the structure of the bottom stem, resulting in the formation of a new bottom stem with enhanced stability. The cell culture alternative splicing patterns of a series of minigenes reveal that the splicing activities of the mutants with destabilizing mutations on the top stem can be compensated in a position-dependent manner by the +19G mutation in the bottom stem. We observed an excellent correlation between the level of exon 10 inclusion and the rate of mechanical unfolding at 10 pN, indicating that the unfolding of the splice site hairpins (to facilitate subsequent binding of U1 snRNA) may be aided by helicases or other proteins.